Methodological aspects of determining the Kazakhstan model of secularism - Sikhimbayeva, D.; Nurmoldina, I. (Eurasian Journal of Religious Studies, 2020)
The article discusses the basic principles of secularity and criteria for determining secularism in the scientific community. The authors analyze the Kazakhstan model of secularism and explore the specifics of state-confessional relations in the Republic of Kazakhstan. To date, the role and position of religion in a post-secular society, as well as the relevance of the issue of secularism, are widely discussed not only in the scientific community but also among the society. As you know, secularism is one of the basic principles of the functioning of modern legal states like Kazakhstan. Since the concepts of “secularism”, “secularity”, and “secularism principles” are not sufficiently studied in Kazakhstani scientific literature, this research attempts to systematically explain these phenomena. The authors of this article reveal the etymological content of the term “secularism” and consider the key obstacles to determine secularism in the studies of leading Western scholars. To compare key issues methods of comparative and etymological analysis were used. This article also discusses the religious situation in Kazakhstan, and state policy in the religious sphere. The practical importance of the study is the analysis of the Kazakhstani model of secularity and making recommendations to determine the principles of secularism.
Keywords: secularity; secularism; religion; principles of secularity; Republic of Kazakhstan; concept